ANALISIS KUALITAS SUMBER DAYA MANUSIA DI BADAN PENGAWASAN KEUANGAN DAN PEMBANGUNAN (BPKP) - Retno Setyowati; Muhammad Mathori (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2016)
The purpose of this research is to identify, evaluate, and analyse the range of factors that impact the quality of human resources at the Finance and Development Supervisory Agency (BPKP); as well as past, present, and future efforts in improving said resources. Research and data collection was conducted at the Finance and Development Supervisory Agency main office in Jakarta (BPKP Pusat), as well as its subsidiary at Local Government level in Special Region of Yogyakarta (BPKP DIY Yogyakarta). Data collection comprised of face to face and written interviews with 43 respondents, which includes: First Secretary at BPKP Pusat, Head of BPKP DIY Yogyakarta, 40 BPKP staff members - 27 from BPKP Pusat and 13 from BPKP DIY Yogyakarta, and 1 expert. The main factor that influences the quality of human resources at the Finance and Development Supervisory Agency (BPKP) is the level of capability and competency possessed by staff, in order for them to perform assigned function and duties at maximum capacity. At present efforts to improve this include specialised education and training held at the main Finance and Development Supervisory Agency training centre, as well as sending staff members to higher formal education and other specialised training - both domestically (within Indonesia) and abroad.